THE RELEVANCE AND TIMELINESS OF PAULO FREIRE’S TEACHINGS - Rodrigues, Walace (Seven Editora, 2025)
This work aims to reflect on the relevance and timeliness of the teachings left by our greatest Brazilian educator: Paulo Freire (1921-1997). His Liberating Pedagogy, his philosophy of education, and his focus on issues in Brazilian education, especially for the most vulnerable (oppressed), are important not only for Brazil but also for several countries that use his teachings. Methodologically, this paper presents itself as a theoretical, reflective, and qualitative bibliographical research, seeking concepts and bases for critical thinking from selected texts. The theoretical reflections raised here seek to engage in a dialogue with the challenges of contemporary education, contributing to the strengthening of pedagogical practices committed to an ethical vision of the world, of the subject , and of Education. DOI: https://doi.org/10.56238/sevened2025.036-069